Editors' Introduction: ECRA Vol. 6, No. 4 - CHAU, Patrick Y. K. (Institutional Knowledge at Singapore Management University, 2007)
This issue features a total of 13 articles. The first four articles are part of a special section on “Intelligent agents in e-services”, edited by Professors William K. Cheung and Jane Y. Hsu under the supervision of Professor Robert J. Kauffman. Summaries of articles appearing in the special section are provided in the guest editors’ introduction. The following is a summary of the nine regular submission articles also published in this issue. The review of these articles was kindly coordinated by Professor Jae Kyu Lee, former Editor in Chief of ECRA. The general submission articles in this issue focus on adoption issues, looking in particular at e-commerce adoption in Asia. They offer new insights on adoption models, using data collected in Korea and Taiwan. They also discuss adoption challenges faced by small businesses in New Zealand, online grocery stores in Singapore, businesses in China, and online portals in developing countries such as Nepal. Other topics covered in this issue include pricing of e-government services, automated e-commerce bargaining technologies, and electronic payment solutions. The first two articles look at models derived from social psychology research to help predict people’s adoption of Web technologies. In “A structural equation model of Internet acceptance in Korea”, Byung Gon Kim, Soon Chang Park and Kyoung Jun Lee present and analyze a model of Internet adoption that integrates Ajzen and Fishbein’s theory of reasoned action (TRA) and its extension by Davis in the technology acceptance model (TAM). The study was performed using data collected from 409 employees of 10 Korean companies spanning five industrial sectors. The authors’ analysis indicates that perceived usefulness and perceived ease of use have an important influence on an individual’s adoption of the Internet, whereas subjective norms, which reflect sensitivity to the opinions and expectations of colleagues, do not seem to be significant. In “Predicting consumer intentions to shop online: An empirical test of competing theories”, Hsiu-Fen Lin compares the TAM model and two variations of the theory of planned behavior (TPB) to predict consumer intentions to shop online. The study is based on data collected from 297 Taiwanese customers of online bookstores. While all of the models provide good predictions of actual online shopping use, a variation of the TPB model with decomposed belief structures increases the explanatory power of behavioral intention and provides an improved method of predicting consumer intentions to shop online. Although developing countries could derive significant value from the Web, most have so far failed to reap many of its potential benefits. Research in this area has received scant attention. In “Barriers to e-commerce and competitive business models in developing countries: A case study”, Nir Kshetri provides a review of barriers to e-commerce in developing countries and discusses the business model of a Nepal-based online provider, Thamel.com, as a source of insight for overcoming some of these barriers. In “Level of Internet use by Chinese businesses: A preliminary study”, Xibao Zhang and Cynthia Moussi present results of a study of Internet adoption by Chinese businesses. Though it is preliminary in nature and based on a convenience sample of Chinese managers, the study suggests that China’s emergence as a major exporting nation is prompting many of its businesses to tap into the Internet. Size seems to play an important role in determining whether a business is connected to the Internet. The study also reveals that Internet adoption in China extends to a broad range of activities. In particular, a number of respondents indicated that they participated in electronic marketplaces to reach international customers. In “The adoption of eCommerce communications and applications technologies in small businesses in New Zealand”, Nabeel Al-Qirim studies the impact of factors adapted from the technology innovation literature on the adoption of e-commerce by SMEs in New Zealand. This includes distinguishing between the adoption of email, use of an intranet, use of an extranet and VPN technology, use of the Internet for EDI, and deployment of a public Web site. In their article titled “A comparative analysis of online grocery pricing in Singapore”, Lydia Gan, Shujia He, Tingli Huang and Jiebin Tan compare the pricing strategies of online and brick-and-mortar grocery stores in Singapore. Contrary to what one might have expected, they find that the online stores have greater price dispersion than their brick-and-mortar counterparts. They also find that brick-and-mortar stores actually change prices more often than their online competitors and that price differences between online and brick-and-mortar stores are not statistically significant. In his article on “A framework for pricing government e-services”, Craig L. Johnson looks at the broad range of services governments are making available online. He argues that governments should take a more principled approach to pricing their services, looking at demand elasticity to maximize overall consumer surplus. This would include segmenting e-services into government-to-citizen (G2C) and government-to-business (G2B) transactions, and determining e-service pricing schedules that reflect the demand elasticity associated with these different services. In “Bargaining strategy formulation with CRM for an e-commerce agent”, C.-C. Henry Chan, Chi-Bin Cheng and Chih-Hsiung Hsu propose a dynamic online pricing mechanism. The mechanism is based on customized bargaining strategies that estimate the potential of individual customers and give larger discounts to those customers with a higher, long-term potential. The proposed solution uses fuzzy reasoning to adapt its bargaining strategy. Empirical results show that this approach is more efficient and results in greater customer satisfaction and loyalty than several competing strategies. In “A new electronic traveler’s check scheme based on one-way hash function”, Horng-Twu Liaw, Jiann-Fu Lin and Wei-Chen Wu propose a new electronic traveler’s check system that uses a one-way hash function to improve efficiency and reduce costs. This new system is shown to effectively support both online and offline usage scenarios. We would like to take this opportunity to thank the special section editors and Professor Jae Kyu Lee for the high quality of their work and for their diligence. Many thanks also to the reviewers for the detailed feedback they provided to the authors, and to the authors for their willingness to improve their papers for publication.